Intimate Partner Violence Risk Assessment and Psycho-criminological Analysis: Development of the RBAC-VPI Risk Measure - Allard, Victoria; Higgs, Tamsin; Giguère, Guy; Bourassa, Christian (Canadian Journal of Criminology and Criminal Justice, 2025)
Intimate partner violence (IPV) has both serious consequences for its victims and high rates of recidivism. Risk assessment measures are an integral part of preventing IPV recidivism. The use of brief IPV-specific measures is particularly relevant in settings, such as corrections, where resources are limited. The RBAC-VPI is a 15-item IPV risk assessment designed as a supplement to general risk measures, making it efficient to use in various settings. Validity was tested in a sample of 222 men in the province of Quebec, Canada convicted of a violent offence where the victim was an intimate partner. Participants were evaluated using the RBAC-VPI, a general risk assessment (RBAC-PCQ), a standalone IPV risk assessment (SARA-V3), and a psychopathy assessment (PCL:SV). The RBAC-VPI showed acceptable reliability and very strong convergent validity with the other measures, most notably with the SARA-V3 (r = .51), while containing fewer items and being quicker to administer. A Rasch model item response theory analysis further supported the validity of the measure’s items. Items showed excellent model fit and a good difficulty distribution. Only two items were identified as redundant and one as less informative. This suggests that the RBAC-VPI is both brief and highly informative.